[Accepted version, unedited] MRSA Carriage among Healthcare Workers in a Vietnamese Intensive Care Unit: A Prospective Cohort Study - Thuy Bich Duong; Minh Cuong Duong; James Campbell; Minh Hoang Van Nguyen; Huu Hien Nguyen; Hanh Thi Bich Bui; Chau Van Vinh Nguyen; Anita Heywood (AboutScience Srl, 2022)
Background: Little is known about the prevalence and patterns of methicillin-resistant Staphylococcus aureus (MRSA) carriage among healthcare workers (HCWs) in Intensive Care Unit (ICU) especially in low-middle income countries like Vietnam. Materials and Methods: A prospective cohort study was conducted on HCWs working at the Adult ICU of the Hospital for Tropical Diseases (HTD), which is among the leading tertiary referral hospitals for infectious disease in Vietnam between 28th October and 20th December 2019. Hand and nasal swabs were collected weekly in eight consecutive weeks for MRSA screening in 55 HCWs. Risk factors for MRSA carriage were obtained using a questionnaire. Results: One third (29.1%, 16/55) of HCWs carried MRSA in their noses or hands. MRSA intermittent hand carriage was documented in 3.6% (2/55) of HCWs. Among 53 HCWs undertaking nasal swabs, 24.5% were MRSA persistent and 5.6% were intermittent carriers. MRSA carriage rate was highest among nursing aids (50%, 4/8). More HCWs with underlying diseases were found to be MRSA carriers compared with those without comorbidities (31.8%, 7/22 vs 27.3%, 9/33). Conclusion: MRSA carriage among HCWs is not rare. The findings highlight an urgent need to review and update the local infection prevention and control measures to prevent MRSA transmission from HCWs to patients.